DIGITAL LITERACY-BASED EDUCATIONAL MANAGEMENT AS A PILLAR OF NATIONAL DEVELOPMENT - Badrus Badrus (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Abstract. This study investigates the development of digital technology literacy within the management of educational institutions. It focuses on identifying the outcomes generated when digital literacy is integrated into institutional management, as well as the strategies employed to develop technologically advanced schools. Adopting a descriptive qualitative approach, data were collected through observation, interviews, and documentation. Data analysis was guided by Miles and Huberman’s framework, encompassing five stages: exploring, sorting, describing, explaining, and predicting. The findings reveal that digital technology literacy significantly contributes to the creation of various educational innovations. These include the establishment of technology-based learning systems, enhanced access to educational resources for both teachers and students, and the implementation of digital infrastructure such as Wi-Fi and digital laboratories. These advancements foster student engagement, satisfaction, and skill development. The strategies identified to cultivate technologically superior schools involve two primary approaches: (1) training educators and students in digital literacy, and (2) continuously organizing digital-based competitions to ensure ongoing skill development and adaptation to emerging challenges. The novelty of this research lies in its emphasis on institutional management through the lens of digital technology integration.